2020
DOI: 10.1038/s41467-020-17376-1
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of human brainstem structures and their involvement in common brain disorders

Abstract: Brainstem regions support vital bodily functions, yet their genetic architectures and involvement in common brain disorders remain understudied. Here, using imaging-genetics data from a discovery sample of 27,034 individuals, we identify 45 brainstem-associated genetic loci, including the first linked to midbrain, pons, and medulla oblongata volumes, and map them to 305 genes. In a replication sample of 7432 participants most of the loci show the same effect direction and are significant at a nominal threshold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…We found that the majority of thalamus-linked loci and genes were associated with only one of the seven volumes, which may suggest at least partly independent genetic architectures. This demonstrates the importance of targeting individual nuclei rather than studying the thalamus as a whole, in line with similar benefits observed for other brain structures 19 , 20 . In addition, we found genetic correlations between the thalamic nuclei and distinct cortical regions.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…We found that the majority of thalamus-linked loci and genes were associated with only one of the seven volumes, which may suggest at least partly independent genetic architectures. This demonstrates the importance of targeting individual nuclei rather than studying the thalamus as a whole, in line with similar benefits observed for other brain structures 19 , 20 . In addition, we found genetic correlations between the thalamic nuclei and distinct cortical regions.…”
Section: Resultssupporting
confidence: 73%
“…We conducted GWAS with PLINK 18 on whole thalamus and the six nuclei volumes accounting for age, age-orthogonalized age-squared, sex, scanning site, intracranial volume, and the first 20 genetic principal components. The thalamic nuclei GWAS also accounted for whole thalamus volume, thus revealing genetic signals beyond commonality in volume 19 , 20 . The thalamic nuclei GWAS were also run without covarying for whole thalamus volume and are presented in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our genetic correlation results indicate that migraine was significantly correlated with mood swings, anxiety, depression, or neuroticism, consistent with a previous genetic correlation analysis study 50 . Thus, these findings suggest that migraine shares common variation risk with psychiatric disorders, such as schizophrenia, for which genome-wide significant loci involved in brain function have been reported 51 , 52 .…”
Section: Discussionmentioning
confidence: 66%
“…To fully elucidate wakeful arousal and associated motor processes, a comprehensive investigation of functional connections of the nuclei involved is needed. Moreover, with the ever-increasing evidence of overlapping functions of several regions (Elvsåshagen et al, 2020;Eser et al, 2018), it is becoming imperative to investigate affected networks rather than single regions. However, the connectivity of arousal brainstem nuclei is understudied in living humans (Bär et al, 2016;Beliveau et al, 2015;Bianciardi et al, 2016;Coulombe et al, 2016), due to the limited sensitivity and spatial resolution of conventional imaging and to the lack of atlases of these deep tiny regions of the brain.…”
Section: Introductionmentioning
confidence: 99%